2011
DOI: 10.1021/ac201838e
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Desorption/Tunable Vacuum–Ultraviolet Time-of-Flight Photoionization Aerosol Mass Spectrometry for Investigating Secondary Organic Aerosols in Chamber Experiments

Abstract: This paper describes thermal desorption/tunable vacuum-ultraviolet photoionization time-of-flight aerosol mass spectrometry (TD-VUV-TOF-PIAMS) for the real-time analysis of secondary organic aerosols (SOAs) in smog chamber experiments. SOAs are sampled directly from atmospheric pressure and are focused through an aerodynamic lens assembly into the mass spectrometer. Once the particles have entered the source region, they impact on a heater and are vaporized. The nascent vapor is then softly ionized by tunable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 82 publications
0
35
0
Order By: Relevance
“…Fang et al used VUV photoionisation in a single-particle aerosol time-of-flight mass spectrometer (ATOFMS) for characterisation of the composition of SOAs produced through photooxidation of toluene in a smog chamber. [48,49] Robinson et al [50] reported coupling of a softer ionisation source with an Aerodyne aerosol mass spectrometer (AMS). In that study, a metastable atom bombardment (MAB) ionisation source was incorporated so the system could be readily switched between MAB and traditionally used electron ionisation (EI).…”
Section: Online Ms Methodsmentioning
confidence: 99%
“…Fang et al used VUV photoionisation in a single-particle aerosol time-of-flight mass spectrometer (ATOFMS) for characterisation of the composition of SOAs produced through photooxidation of toluene in a smog chamber. [48,49] Robinson et al [50] reported coupling of a softer ionisation source with an Aerodyne aerosol mass spectrometer (AMS). In that study, a metastable atom bombardment (MAB) ionisation source was incorporated so the system could be readily switched between MAB and traditionally used electron ionisation (EI).…”
Section: Online Ms Methodsmentioning
confidence: 99%
“…The mass spectra of R-(+) limonene obtained at different lower energies are also useful to analyze the products of SOA formed during the photooxidation and photodecomposition of limonene in the (environmental) smog chamber. [12,13] In order to understand the photoionization of these molecules, two photoionization processes should be considered:…”
Section: Introductionmentioning
confidence: 93%
“…Due to the importance of these molecules, an understanding of their mass spectra obtained by tunable vacuum ultraviolet (VUV) synchrotron radiation is required, as well as a need to investigate their basic properties such as ionization energy (IE), the appearance energies (E AE ) of the ions formed during fragmentation. The mass spectra of R‐(+) limonene obtained at different lower energies are also useful to analyze the products of SOA formed during the photooxidation and photodecomposition of limonene in the (environmental) smog chamber …”
Section: Introductionmentioning
confidence: 99%
“…Tunable VUV photoionisation reduces fragmentation of SOA constituents prior to analysis, which greatly simplifies the observed mass spectra. Using this technique, Fang et al conducted detailed characterisation of the composition of SOA produced through photooxidation of several VOCs in a smog chamber [133,134]. It has been demonstrated that accurate measurement of the ionisation energies of individual SOA constituents provides important structural information that is difficult to obtain using other techniques.…”
Section: Laser Desorption Ionisation Mass Spectrometrymentioning
confidence: 99%